Parental LTRs are important in a construct of a stable and efficient replication-competent infectious molecular clone of HIV-1 CRF08_BC. - Qiwei Zhang (Public Library of Science (PLoS), 2012)
Circulating recombinant forms (CRFs) of HIV-1 have been identified in southern China in recent years. CRF08_BC is one of the most predominant subtypes circulating in China. In order to study HIV subtype biology and to provide a tool for biotechnological applications, the first full-length replication-competent infectious molecular clone harboring CRF08_BC is reported. The construction of this clone pBRGX indicates that a moderate-copy number vector is required for its amplification in E. coli. In addition, it is shown that the parental CRF08_BC LTRs are important for generating this efficient replication-competent infectious clone. These observations may aid in the construction of infectious clones from other subtypes. Both the pBRGX-derived virus and its parental isolate contain CCR5 tropism. Their full-length genomes were also sequenced, analyzed, compared and deposited in GenBank (JF719819 and JF719818, respectively). The availability of pBRGX as the first replication-competent molecular clone of CRF08_BC provides a useful tool for a wide range of studies of this newly emergent HIV subtype, including the development of HIV vaccine candidates, antiviral drug screening and drug resistance analysis.